Given differential equation is "z-px-qy-p^2-q^2=0"
Then, "f(x,y,z,p,q) = z-px-qy-p^2-q^2=0"
"\\frac{dx}{-\\frac{\\partial f}{\\partial p}} = \\frac{dy}{-\\frac{\\partial f}{\\partial q}}=\\frac{dz}{-p\\frac{\\partial f}{\\partial p}-q\\frac{\\partial f}{\\partial q}}=\\frac{dp}{\\frac{\\partial f}{\\partial x}+p\\frac{\\partial f}{\\partial z}}=\\frac{dq}{\\frac{\\partial f}{\\partial y}+q\\frac{\\partial f}{\\partial z}}"
Then,
"\\frac{\\partial f}{\\partial p} = -(x+2p)", "\\frac{\\partial f}{\\partial q}=-(y+2q)", "\\frac{\\partial f}{\\partial x} =-p" , "\\frac{\\partial f}{\\partial y}=-q" , "\\frac{\\partial f}{\\partial z} = 1"
Putting values, we get,
"\\frac{dx}{x+2p} = \\frac{dy}{y+2q}=\\frac{dz}{p(x+2p)+q(y+2q)}=\\frac{dp}{-p+p}=\\frac{dq}{-q+q}"
"\\frac{dx}{x+2p} = \\frac{dy}{y+2q}=\\frac{dz}{px+qy+2p^2+2q^2}=\\frac{dp}{0}=\\frac{dq}{0}"
Taking second last term, "dp = 0 \\implies p = a" (1)
taking last term, "dq=0 \\implies q=b" (2)
Then, "dz = pdx+qdy = adx+bdy"
integrating both sides, "z = ax+by+c" (3)
Now, equation will be,
"ax+by+c = ax+by+a^2+b^2"
"\\implies c = a^2+b^2"
Hence, "z = ax+by+a^2+b^2"
Comments
Leave a comment